2001
DOI: 10.1046/j.1440-1754.2001.00661.x
|View full text |Cite
|
Sign up to set email alerts
|

Childhood infections in the tropical north of Australia

Abstract: In the tropical north of Australia there are high rates of infections in Aboriginal children living in remote communities. In addition to the burden of respiratory infections, diarrhoeal disease and skin sepsis, there are high rates of acute rheumatic fever, outbreaks of poststreptococcal glomerulonephritis and gonococcal conjunctivitis, endemic trachoma and various intestinal parasites. A number of infections generally restricted to the tropics are also present and can cause disease in both indigenous and non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…Reported prevalences ranged from 2.5% to 30% in the Northern Territory, 0% to 25% in South Australia and 18% to 53% in Western Australia. Currie and Brewster [105] reported that in the tropical north of Australia there were high rates of gonococcal conjunctivitis and endemic trachoma in Aboriginal children in remote communities.…”
Section: Vision Screening Of Indigenous Australian Childrenmentioning
confidence: 99%
“…Reported prevalences ranged from 2.5% to 30% in the Northern Territory, 0% to 25% in South Australia and 18% to 53% in Western Australia. Currie and Brewster [105] reported that in the tropical north of Australia there were high rates of gonococcal conjunctivitis and endemic trachoma in Aboriginal children in remote communities.…”
Section: Vision Screening Of Indigenous Australian Childrenmentioning
confidence: 99%
“…Aboriginal infants also have a higher burden of illness and hospitalisation than non-Aboriginal infants [5]. Despite improvements in perinatal mortality [6] incidence rates of certain infectious diseases continue to be among the highest in the world [7]. In the Northern Territory (NT), where Aboriginal Australians comprise 30% of the population [8], respiratory and diarrhoeal diseases are the leading causes of hospitalisation for Aboriginal infants and children [9].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Scabies is endemic in some Aboriginal populations, with a prevalence reportedly as high as 50% in children, and 25% in adults. 1 Scabies underlies up to 70% of streptococcal skin infections.…”
Section: Introductionmentioning
confidence: 99%
“…3 Impetigo/pyoderma (synonymous with skin sores in published literature) is seen in 10-70% of Aboriginal children in remote communities. 1,2 Several studies have found that the primary pathogen causing impetigo is group A streptococcus (GAS), with 80-93% of lesions swabbed being GAS-positive. 1,4,5 Streptococcal skin infection can lead to post-streptococcal glomerulonephritis (PSGN) and acute rheumatic fever (ARF).…”
Section: Introductionmentioning
confidence: 99%